Numerical model characterization of the sound transmission mechanism in the tympanic membrane from a high-speed digital holographic experiment in transient regime - García-Manrique-Ocaña, José Manuel; Furlong, Cosme; González-Herrera, Antonio; Cheng, Jeffrey T. (Elsevier, 2023)
A methodology for the development of a finite element numerical model of the tympanic membrane (TM) based on experiments carried out in the time domain on a cadaveric human temporal bone is presented. Using a high-speed digital holographic (HDH) system, acoustically-induced transient displacements of the TM surface are obtained. The procedure is capable to generate and validate the finite element model of the TM by numerical and experimental data correlation. Reverse engineering approach is used to iden- tify key material parameters that define the mechanical response of the TM. Finally, modal numerical simulations of the specimen are performed. Results show the feasibility of the methodology to obtain an accurate model of a specific specimen and to help interpret its behaviour with additional numerical simulations.
Keywords: Sonido - Transmisión; Oído; Finite element model; Acoustic–structural coupled analysis; Tympanic membrane; High-speed digital holographic; Sound transmission